2018
DOI: 10.1152/ajpheart.00597.2017
|View full text |Cite
|
Sign up to set email alerts
|

TIMP3 deficiency exacerbates iron overload-mediated cardiomyopathy and liver disease

Abstract: Chronic iron overload results in heart and liver diseases and is a common cause of morbidity and mortality in patients with genetic hemochromatosis and secondary iron overload. We investigated the role of tissue inhibitor of metalloproteinase 3 (TIMP3) in iron overload-mediated tissue injury by subjecting male mice lacking Timp3 ( Timp3) and wild-type (WT) mice to 12 wk of chronic iron overload. Whereas WT mice with iron overload developed diastolic dysfunction, iron-overloaded Timp3 mice showed worsened cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 66 publications
(99 reference statements)
1
23
0
Order By: Relevance
“…TIMP3 deficiency was previously associated with inflammatory cells accumulation 46 and exacerbated liver injury through enhanced inflammation and IL1‐ß expression 47,48 . Our observations have consistently shown that IL1‐ß and TIMP3 expressions are inversely correlated in the mouse model of CCl4‐induced acute liver injury.…”
Section: Discussionsupporting
confidence: 77%
“…TIMP3 deficiency was previously associated with inflammatory cells accumulation 46 and exacerbated liver injury through enhanced inflammation and IL1‐ß expression 47,48 . Our observations have consistently shown that IL1‐ß and TIMP3 expressions are inversely correlated in the mouse model of CCl4‐induced acute liver injury.…”
Section: Discussionsupporting
confidence: 77%
“…In both groups of vertebrates, long-lasting hypoxia-induced polycythemia can lead to splenomegaly, arterial congestion, blood vessel wall thickening, increased hemolysis, and/or hemochromatosis [34,[39][40][41][42]. With increased red blood cell recycling, the resulting iron excess can accumulate as hemosiderin in the liver, pancreas, and spleen where it can induce nonspecific inflammation and fibrosis [41,[43][44][45]. As part of the inflammatory response, the accumulated iron attracts macrophages that remove excess red blood cells, promote iron recycling, and sequester iron, all in an effort to defend tissues against iron overload and related cellular toxicity [21,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Too much iron can also be deposited in human tissues, causing a condition called hemochromatosis [21]. Studies have linked iron overload to hepatic disease [22], heart disease [23], diabetes [24], and leukemia [25].…”
Section: Relationship Between Iron and Tumormentioning
confidence: 99%